Adipocyte-Specific Inhibition of Mir221/222 Ameliorates Diet-Induced Obesity Through Targeting Ddit4 - Yamaguchi, Satoshi; Zhang, Dongxiao; Katayama, Akihiro; Kurooka, Naoko; Sugawara, Ryosuke; Albuayjan, Haya Hamed Hassan; Nakatsuka, Atsuko; Eguchi, Jun; Wada, Jun (Frontiers in Endocrinology, 2022)
MicroRNAs expressed in adipocytes are involved in transcriptional regulation of target mRNAs in obesity, but miRNAs critically involved in this process is not well characterized. Here, we identified upregulation of miR-221-3p and miR-222-3p in the white adipose tissues in C57BL/6 mice fed with high fat-high sucrose (HFHS) chow by RNA sequencing. Mir221 and Mir222 are paralogous genes and share the common seed sequence and Mir221/222AdipoKO mice fed with HFHS chow demonstrated resistance to the development of obesity compared with Mir221/222flox/y. Ddit4 is a direct target of Mir221 and Mir222, and the upregulation of Ddit4 in Mir221/222AdipoKO was associated with the suppression of TSC2 (tuberous sclerosis complex 2)/mammalian target of rapamycin complex 1 (mTORC1)/S6K (ribosomal protein S6 kinase) pathway. The inhibition of miR-221-3p and miR-222-3p linked to reduced adipogenesis and lipogenesis, and it may be a potential candidate for miRNA-based therapy.